In silico identification of silent primycin biosynthetic gene clusters within the family Pseudonocardiaceae - Márk Kovács-Valasek; Csaba Fekete; Andrea Kovács-Valasek (Heliyon)
In the global effort to discover or design new effective antibiotics to fight infectious diseases, the increasingly available multi-omics data with novel bioinformatics tools open up new horizons for the exploration of the genetic potential of bacteria to synthesize bioactive secondary metabolites. Rare actinomycetes are a prolific source of structurally diverse secondary metabolites that exhibit remarkable clinical and industrial importance. Recently several excellent genome mining tools have been available for identifying biosynthetic gene clusters, however in cases of poor-quality sequences and inappropriate genome assembly, these tools are not always able to identify the corresponding gene clusters. In this context, based on the previously characterized primycin biosynthetic gene cluster (PBGC) of the Saccharomonospora azurea SZMC 14600 strain an extended genome mining analysis was performed to advance the industrial application of unexplored taxa outside the Saccharomonospora genus. Further improvement of S. azurea PBGC revealed 28 clustered genes including core sequences for type I polyketide synthase. Application of PBGC core elements and targeted genome mining workflows revealed three species from the family Pseudonocardiaceae that can be considered potential candidates for primycin production, despite the fact that the discovered biosynthetic gene clusters were silent under the currently applied laboratory-culture condition. The findings presented here demonstrate the potential of an in silico toolkit and draw attention to the importance of awakening the dormant biosynthetic potential.